The Development of Instructional Model in Geography According to Active Learning Focused on Case Study Based Learning to Enhance Analytical Skills According to Marzano’s Taxonomy for Elementary School Students - Lertchanadecha, Thayida; Kitroongrueng, Poranat (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The problem with geography instruction nowadays is that students lack the skills to integrate the knowledge into their daily lives. Furthermore, if the students are provided with a learning process that they can perform by themselves and practice using in different situations, they can improve their analytical thinking skills and adapt to their daily lives. Therefore, this research aimed to develop the instructional model in geography according to active learning, which was focused on case study-based learning to enhance analytical skills according to Marzano’s taxonomy for elementary school students. Methodology: The methodology was divided into two steps. 1) The researcher collected the fundamental information, problems, and necessities and then studied and analyzed the concepts, theories, and related research. Moreover, the researcher interviewed the target groups, including 5 experts, 4 school administrators, 8 elementary teachers of social studies, the religion and culture department, and 15 elementary students. 2) The researcher developed the instructional model and verified its quality using a focus group discussion containing seven experts. The data was analyzed using mean (M), standard deviation (SD), and content analysis. Results: From evaluating the instructional model in geography according to active learning, which was focused on case study-based learning to enhance analytical skills according to Marzano’s taxonomy for elementary school students, it was found that the overall appropriateness was at the highest level (M = 4.57, SD = 0.09). Conclusion: It could be seen that the instructional model in geography according to active learning, which was focused on case study-based learning to enhance analytical skills according to Marzano’s taxonomy for elementary school students (ABABA Model), contained 5 elements. 1) There are five principles containing: 1.1) performing, 1.2) interaction, 1.3) data collection, 1.4) analysis, and 1.5) implementation. 2) The purpose is to enhance analytical skills according to Marzano’s taxonomy for elementary school students. 3) 5 instructional steps: 3.1) assigning: A, 3.2) brainstorming: B, 3.3) adjusting problems: A, 3.4) briefing and presenting: B, and 3.5) assessing: A. 4) 2 methods of assessment and evaluation: 4.1) formative assessment, and 4.2) summative assessment. To verify the students’ analytical skills after studying, the tests of analytical skills and assessment were conducted according to Marzano’s taxonomy, including 4.2.1 matching, 4.2.2 classifying, 4.2.3 error analysis, 4.2.4 generalizing, and 4.2.5 specifying. Furthermore, 5) The support systems: 5.1) the social system that teachers must facilitate the atmosphere to support the interaction with fellows and teachers. 5.2) supporting system that teachers must provide the contents, equipment, instructional media, problems, or real-life situations for students. 5.3) a response system that teachers can facilitate for performing learning activities, providing suggestions, and enhancing learning motivation.